Pengaruh Kepercayaan, Promosi Online dan Harga Terhadap Keputusan Pembelian Konsumen di Poljammart - wira amanda, viona; Handoko , Dedi; junaidi (LP2M Politeknik Jambi, 2026)
This study aims to determine the effect of trust, online promotion, and price on consumer purchasing decisions at Poljam Mart. The research method used was quantitative with a descriptive-verificative approach. The sample consisted of 99 respondents selected using a non-probability sampling technique with the accidental sampling method. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. The results of the study indicate that trust, online promotion, and price have a positive and significant effect on consumer purchasing decisions, both partially and simultaneously. The t-values for trust, online promotion, and price were 5.139, 4.110, and 2.602 respectively, with significance values < 0.05. Simultaneously, the F-value obtained was 82.289 with a significance level of 0.000 < 0.05, indicating that the three independent variables jointly have a significant effect on purchasing decisions. The coefficient of determination (R²) was 0.717, indicating that 71.7% of purchasing decisions are influenced by trust, online promotion, and price, while the remaining 28.3% are influenced by other variables outside this study.